PLANEACIÓN ESTRATÉGICA APLICADA A LA COOPERATIVA DE AHORRO Y CRÉDITO SAN SEBASTIAN DE LA CIUDAD DE LOJA. PERIODO 2017-2021 - Ambuludi Angamarca, Gimena Marilú (2018)
The research work was carried out in the Savings and Credit Cooperative San Sebastian in which its members collaborated with the necessary information for the realization of the thesis entitled "STRATEGIC PLANNING APPLIED TO THE SAN SEBASTIAN SAVINGS AND CREDIT COOPERATIVE OF THE CITY OF LOJA PERIOD 2017-2021 ", with the purpose of establishing alternative plans and tools, where the union of internal resources prevails with the opportunities of the business environment, with the goal of reducing internal weaknesses and threats that may affect the development of the activities of the Cooperative. In order to comply with the objectives in the first instance, a diagnosis was made of the current situation of the entity under study, tending to find the reference point for the formulation in the strategic planning 2017-2021; Through a survey conducted to the entity to detect the main problems faced by the cooperative, the collection of information was carried out, through surveys aimed at managers, staff and partners of the institution, as well as the pearls monitoring system for the years 2014. -2015, with the purpose of finding alternative solutions for the improvement of the same and in this way to know the strengths and weaknesses of the institution. The collection of bibliographic information was used to obtain political, economic, legal and social information, to perform an analysis of the external environment, thus obtaining the opportunities and threats that the entity has. Once the information acquired was obtained, the MEFI and MEFE matrix were prepared, obtaining a result of 1.97 and 2.17 of the corresponding weighted average, demonstrating that it has a very weak internal position, since its weaknesses are much greater than its strengths and the entity is not effectively taking advantage of existing opportunities and minimizing the possible negative effects of external threats. Then, with the data obtained in the analysis of the current situation and strategic analysis, the SWOT matrix and the SWOT analysis matrix were elaborated, where the different strategies that were applied to comply with the strategic objectives were determined; Likewise, the MCPE was built, classifying the strategies with the highest score, where the following stand out; develop training programs for the personnel, administrative and 5 directive of the COAC aimed at strengthening their development in their functions and activities, design a manual of functions, which allows to properly guide and distribute the functions of the staff, design and disseminate learning campaigns on issues Financial education and entrepreneurship, involving all the partners of the entity and the general public, make an advertising plan, the products and services offered, develop new agreements with associations to generate new partners. Finally, the Annual Operative Plan POA was prepared, this being a very useful management tool to meet the objectives of the cooperative, which details the strategies, activities and actions to be carried out to meet the objectives set, those responsible, the term for the execution of each action, and define the necessary budget and appoint responsible; as well as carrying out the necessary follow-up to all the actions and evaluating the management, as planned.